Arteriography after embolization before distal pancreatectomy with en bloc celiac axis resection. Issue 6 (2nd November 2015) - Yamagami, Takuji; Yoshimatsu, Rika; Kajiwara, Kenji; Ishikawa, Masaki; Murakami, Yoshiaki; Uemura, Kenichiro; Awai, Kazuo
Abstract: Objective : To evaluate hemodynamics by arteriographic examinations with and without CT in the stomach wall and liver after preoperative embolization to redistribute blood flow to the stomach and liver, which is unified to be supplied from the superior mesenteric artery, before distal pancreatectomy with en bloc celiac axis resection (DP-CAR).Material and methods : In six patients with locally advanced cancer of the pancreatic body in whom DP-CAR was planned, the left gastric artery and common hepatic artery were embolized with coils. Celiac arteriography and superior mesenteric arteriography with and without CT were performed after embolization.Results : In all six patients, intrahepatic arteries and the left gastric artery were not visualized on celiac arteriography. On both superior mesenteric arteriography and CT obtained while contrast medium was infused via the superior mesenteric artery and which was performed immediately after embolization procedures, the right gastric artery, gastroepiploic artery, gastroduodenal artery, and all hepatic arterial branches were clearly detected. Also the distal part of the left gastric artery close to the embolized point was detected with at least one of the imaging modalities.Conclusion : It was clarified radiologically that preoperative embolization results in increased blood supply to the stomach wall and liver through the pancreatic arcade.